NATIONAL AND WORLD EXPERIENCE IN YOUTH EDUCATION - Ruziyev Alisher Xolmurodovich (Sciental Journals Publishing, 2025)
This article analyzes the role and significance of national values and world experiences in the upbringing of young people. The study examines traditional methods of upbringing and modern approaches to spiritual, moral and social education of the younger generation, as well as modern approaches based on the experience of developed countries. It also shows effective ways to harmonize the national education system with global pedagogical practices. The article identifies cooperation between the family, educational institutions and society as a key factor in the upbringing of young people. The research results include scientific and practical recommendations directed to improving youth education.
Keywords: Education, moral education, legal education, mental education, aesthetic education, physical education, labor education.